Operational and design factors in air staging and their effects on fouling from biomass combustion - Elsebaie, Akram; Zhu, Mingming; Al-Abdeli, Yasir M. (MDPI, 2024)
The global transition towards a carbon-neutral economy highlights the potential of biomass as a renewable fuel source. However, the sustainability of biomass energy systems is challenged by its complex fouling behaviours during combustion. This study investigates the impact of air staging on mitigating fouling in biomass combustion. By optimising the secondary-to-total air flowrate ratio (Qs/Qt) and the positioning of secondary air, this research investigates the impact of operational and design parameters on fouling deposits in biomass combustion. A fixed-bed combustor was used for the experiments, with hardwood pellets as fuel. This study employed TGA and SEM to analyse the fouling deposit samples’ chemical composition and morphology. First, visible inspection established that the inclination of fouling matter to accumulate on cooled deposition pipes is indeed sensitive to Qs/Qt. The results show that lower Qs/Qt ratios (<0.50) lead to heavier, stickier fouling. Peak temperatures in the fuel bed increase with higher Qs/Qt, enhancing the combustion efficiency and affecting the fouling characteristics. SEM analysis further shows that higher Qs/Qt ratios produce finer, more dispersed fouling particles, whereas lower ratios result in larger, more cohesive particles. These findings provide actionable insights for enhancing the sustainability of biomass energy systems and minimising their environmental impact.
Keywords: 41 Environmental Sciences; 40 Engineering; 4104 Environmental Management; 7 Affordable and Clean Energy; 13 Climate Action; sustainable biomass energy; air staging optimisation; biomass combustion; fouling mitigation; fixed-bed combustor; carbon-neutral technologies